Effects of a play-based approach on psychosocial variables in federated long- and middle-distance athletes - Alfonso Valero-Valenzuela; Luz Amalia Hoyos Cuartas; Diego Andrés Heredia-León; Patxi León-Guereño (Frontiers in Psychology)
IntroductionConsidering the theory of self-determination and its relationship with human motivation and the play-based approach (PBA), a training program is implemented in young middle and long-distance running athletes with play activities (simple tasks with rules in a ludic mood). The objectives were (1) to analyze the effects of a PBA on the autonomy support interpersonal teaching style (ASITS) perceived by athletes, the psychological variables of satisfaction of basic psychological needs, motivation, enjoyment and intention to continue practicing athletics and depending on sex, and (2) know the athletes' perception of this methodology after the intervention.MethodQuasi- experimental design with a sample of 50 athletes (27 women and 23 men) with 17.22 average of age and federated at the regional level.InstrumentsAutonomy Support Scale (ASS), Psychological Need Satisfaction in Exercise Scale (PNSE), Behavior Regulation in Sports Questionnaire (BRSQ), Measure of Intention to be Physically Active (MIPA) and Intrinsic Satisfaction in Sports Questionnaire (ISSQ).ResultsSignificant changes were identified in favor of the experimental group compared to the control group in ASITS and autonomous motivation. Over time, only the experimental group showed positive changes in the ASITS variable, self-determination index, autonomous motivation, and intention to continue practicing athletics. The women in the experimental group presented higher values in the self-determination index, autonomous motivation and intention to continue practicing athletics, while the women in the control group only in the ASITS variable in the pre-test. The young people who practiced playing during the warm-up reported high levels of fun and motivation, and interest in the activity, as well as concern about being prepared for the main part of the session.DiscussionIt is suggested to athletic trainers to use a PBA in athletics groups at a regional level to promote an ASITS and its positive consequences at both a psychosocial and cognitive level, although new studies are required, and of longer duration to be able to contrast these findings and their effects on athletic performance.